PERAN CYBERLOAFING SEBAGAI MODERATOR DALAM MENINGKATKAN JOB PERFORMANCE - silvana muchsinati, Evi; Hasnita, Revi; Sudhartio, Lily (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This study aims to evaluate and analyze the effect of job stress, boredom, and workplace ostracism on job performance, with cyberloafing behavior as a moderating variable, on Riau Islands Provincial Government employees. The approach used is quantitative, involving the distribution of questionnaires to 1,200 employees from 12 Regional Apparatus that experienced a decrease in SAKIP scores in 2023. The sample size consisted of 300 employees, determined using the Slovin formula calculation. Data analysis was carried out using SmartPLS version 3.0 software with the Structural Equation Modeling (SEM) method. The research findings show: (1) Job Stress has a positive and significant influence on Job Performance; (2) Boredom has a negative and significant influence on Job Performance; (3) Workplace Ostracism has a negative and significant impact on Job Performance; (4) cyberloafing behavior has no moderating effect on the relationship between job stress and Job Performance; (5) cyberloafing behavior moderately strengthens the relationship between Boredom and Job Performance significantly; and (6) cyberloafing behavior moderately weakens the relationship between Workplace Ostracism and Job Performance significantly